EVOLUTION OF THE SOUTHERN MARGIN OF THE DONBAS (UKRAINE) FROM DEVONIAN TO EARLY CARBONIFEROUS TIMES - McCann T.; Saintot A.; Chalot-Prat F.; Kitchka A.; Fokin P.; Alekseev A. (My University, 2003)
A Devonian-Early Carboniferous succession comprising thick clastic and carbonate sediments with interbedded volcanics was examined along the southern margin of the Donbas fold belt. Ukraine. Following initial rifting and subsidence, a continental (fluvial, lacustrine) succession was established. This first phase of synrift activity (Eifelian) was accompanied by the extrusion of basalts. In Late Givetian-early Famennian times, half-graben development was pronounced and a series of E-W-trending half-grabens were formed, along with coeval volcanic activity. Subsequent basin subsidence led to the establishment of a broad marine carbonate platform across the region (Late Famennian-Tournaisian-early Viséan). Renewed uplift led to partial exposure and karstification of the platform. This was accompanied by trachyte intrusion and extrusion. The overlying chert-rich unit was probably deposited under lacustrine conditions, although a shelf environment has also been suggested. Renewed tectonic activity along the main basin-bounding fault resulted in the synsedimentary deformation of this unit.
Keywords: Carboniferous; Devonian; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Devonian; Палеозой::Девонская